Learning styles and teaching styles determine students’ academic performances - Nithya Dewi, Subramaniam Chetty; Lina, Handayani; Noor Azida, Sahabudin; Zuraina, Ali; Norhasyimah, Hamzah; Nur Shamsiah, Abdul Rahman; Shahreen, Kasim (Institute of Advanced Engineering and Science, 2019)
Individuals learn in different ways using several learning styles, but lecturers may not always share material and learning experiences that match students’ learning preferences. Mismatches between learning and teaching styles can lead to disappointment with students are taking, and lead to underperformance among them. The aim of this study is to identify the learning styles of the students enrolled in Universiti Malaysia Pahang who were registered in Programming Technique course and to investigate the relationship between students’ learning styles and teachers’ teaching styles. Five lecturers and 251 students were involved in the study as participants and. Data from students were collected using Leonard, Enid’s VAK Learning Style Survey. Meanwhile, the teaching styles of the lecturers were identified using Grasha and Reichmann’s Teaching Style Survey. The findings revealed that majority of the student’s preferred visual learning style. The result also shows that the lecturers’ teaching styles give an impact towards the students’ academic performance. From this study, we can conclude that teaching styles have significant impacts on students’ learning styles and academic performances.